(3aVd GdYQH Ydi GdYLes - (3YHO Gddg Hf eSde Hf bJjHI GdOjnfnhQqj, CHh eMeO, GHf obnJrjnHI, J (B276 (3g` s
(3ChdgG (B:s
(3Chd eG ajgG CKfGA GdcdGe Ydi JfGhd GdWYGe hBOGHg heG hQO ef CNHGQ GdfHi Udi Gddg Ydjg hSde ai aVd GdYQH s
(3BNQgG (B:s
(3HBNQ GdcJGH s
(3bUO HgPG GdcJGH dJfHjI hGdOdGdIs
(3hOaY GdNUe YeG jfSH Edi GdYQH ef GdLaGA hGdZHGhIEdNs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B137s
Keywords: (3GdSjGSI hGdGLJeGYs